1947
DOI: 10.1017/s0022172400014169
|View full text |Cite
|
Sign up to set email alerts
|

Variation, diurnal and over longer periods of time, in blood haemoglobin, haematocrit, plasma protein, erythrocyte sedimentation rate, and blood chloride

Abstract: Although the composition of blood is assumed to be constant within narrow limits, fluctuations in concentration of its constituents have been found by many observers over the period of a day or longer. Shaw (1927), Jores (1934) and others describe daily fluctuations in the white corpuscles, and Sabin et al. (1925) found similar changes in the blood platelets.The literature dealing with diurnal fluctuations in the red blood corpuscles (R.B.C.) is already large and has been recently reviewed by Branwood (1946)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

1950
1950
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 19 publications
2
7
0
1
Order By: Relevance
“…As with pre-exercise conditions, fibrinogen, albumin and total protein were resistant to biorhythmic influences during sub-maximal endurance exercise. These data are consistent with earlier reports [26], in which suggested that significant changes in plasma proteins are absent during normal waking hours of 07:00 to 10:00. In addition to baseline values, the plasma protein responses to sub-maximal exercise were not affected by time of day.…”
Section: Discussionsupporting
confidence: 94%
“…As with pre-exercise conditions, fibrinogen, albumin and total protein were resistant to biorhythmic influences during sub-maximal endurance exercise. These data are consistent with earlier reports [26], in which suggested that significant changes in plasma proteins are absent during normal waking hours of 07:00 to 10:00. In addition to baseline values, the plasma protein responses to sub-maximal exercise were not affected by time of day.…”
Section: Discussionsupporting
confidence: 94%
“…A definite trend was not found in hs-cTnI in healthy individuals, possibly because CVa in this group was much higher than the biological variation. Diurnal variation is indeed a common finding for many biological constituents (39,40 ), and we assume that the declining values seen in the current study represent a part (i.e., 6 h) of the diurnal variation of hs-cTn. In principle, the calculated RCV found in our study is valid only between 08:30 and 14:30, because the magnitude and direction of diurnal variation assumed during the 24-h cycle is unknown.…”
Section: Discussionmentioning
confidence: 77%
“…Спазм коронарных артерий ведет к сни-жению толерантности к физическим нагрузкам, провоци-рует ангинозные боли и может привести к разрыву атеро-склеротических бляшек, образованию нестабильных бля-шек с последующим развитием тромбоза. По данным лите-ратуры, в холодное время года у здоровых людей и пациен-тов с заболеваниями сосудов отмечена гемоконцентрация [24][25][26][27][28][29], повышение уровня прокоагулянтов и маркеров активации гемостаза (фактор свертывания крови VIII [30], фактор Виллебранда [30], фибриноген [23,24,30], D-димер [31], маркеров воспалительной реакции (СОЭ [20,28], C-реактивный белок [31,23], ИЛ-1,ИЛ-6 [23]), снижение концентрации прокоагулянтов (протеин С [24]), антиокси-дантов (витамин D [29]). …”
Section: ил козловская и соавтunclassified